Economic Surplus, Social Reproduction, Nurturance and Love - O'Hara, Phillip (Springer, 2010)
This paper examines the contributions of James Ronald Stanfield to social and political economy. We start the analysis with Stanfield’s contribution to institution building through his education of PhD students, building a graduate program in political economy, and through the associations of social and political economy. Then we go on to scrutinise his creative developments and applications of the notions of economic surplus and social reproduction. This is followed by his extensive work on Karl Polanyi and the disembedded economy. Finally we explore his path-breaking analysis of the great capitalist restoration, the nurturance gap and love. Stanfield was one of the greatest institutionalists and social economists of the last hundred years, and these four areas of energetic creativity are his prime achievements in the area.